A comparative content analysis of ABS-CBN's CCTV Patrol and GMA-7 Hulicam segments from June-December 2013 - Hernandez, Jeanne Camille B.; Salvador, Mark Conrad C. (2014)
"This study presents data and analysis of the pervasiveness and widespread use of surveillance cameras in the country. In the span of a few year, the use of this relatively new technology has grown at a fast pace, and media organizations in the Philippines have began to tap this new technology in their news programs, specifically in crime-reporting. This study aims to answer the question, "What are the ethical dilemmas that the production team and contributors experience in the use of Closed Circuit Television (CCTV) in news reporting by ABS-CBN and GMA-7?" The researchers used content-analysis and focus interviews as its research methods. The study will also look into the issues of privacy, security and journalism ethics in the use of CCTV in news reporting. Together with the Agenda-Setting Theory, they looked into how media organizations treat these materials in terms of the claim that it delivers public service even though there may be ethical issues involved."